INFLUENCE OF FIRM'S SIZE AND AGE ON LEVERAGE OF LISTED FINANCIAL FIRMS IN NIGERIA - Solanke Abiola Abosede; Mohammed Yabagi Ibrahim, (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
Size and age impact firm leverage in any organisation, being in the financial or non-financial sector. Little concerning how these firm characteristics affect leverage in the Nigeria Financial sector is known. This study examines the firm size and listing age on the leverage of listed financial firms in Nigeria. Data extracted from annual accounts of 49 financial firms over 12 years (2008-2019). Descriptive statistics and inferential statistics wear used to estimate the relationship between a firm's size, listening age, and leverage. The study reveals that firm size is negatively and significantly related to the firm's leverage. Age has a positive and significant effect on the leverage of the financial sector. The study suggests that firms continuously employ debt capital to benefit from available tax shields, ultimately enhancing profitability. The limitation of the study is that the survey covered only financial institutions listed on the Nigeria stock exchange as of 2019. The study contributed to the existing finance theory and literature by using empirical evidence from an emerging market to bridge the gap in knowledge of the influence of size and age on the leverage of financial firms.